Os nexos que tecem as competências de futuros enfermeiros - Tacahashi, Dirce Setsuko (2006)
This study lies on the premise that the pedagogic action is a social practice of such fact: the scenery is undissociable, complex and contradictory, creating a series of connections that constitutes the future nurse's competences. The subject that guided this study is thus put up as: The reality in the which both the visible phenomena - unexpectation, failures, conquests and celebrations - and the invisible phenomena - the emotions, motives, necessities, interests - do they integrate condition the individual's formation? The procedure of the research participant action was built through a reflexive conversation with the situation. To understand the genesis of the social subjectivity that it produces the systems of senses in the educational action took us to three aspects that constituted the theoretical-hypothetical-constructiveinterpretative spaces: 1) we appealed starting from the history of the nursing currícula, and we confronted with historical facts of the Course of Nursing of PUCSP. 2) the variables: the difference between the theory and the practice and the subjective configurations of the social space in which the learning takes place, 3) Finally, we have anchored in the present time and focused in whatever moves us for a change in the construction of the new currículum, it is right here that the past and the present are founded and the present is seen to the light of the History. When deciphering the entanglements of the facts that happen while weaving the future nurse's competences we borrow glances and other people's dialogues (students, work mates and experts in the subject) that in spite of the distance and the memories of the past, with their doubts and propositions, they contributed to elaborate arguments to reduce the dissatisfaction of that scenery that now we are presented to and to offer subsidies to decipher the concerns, that at this very moment time are living, of the curricular reform of the Course of Nursing of PUC-SP to adapt to the new Curricular Directives